Thought-Shaping, Reflection and the Refractive Element - Paans, Otto (Philosophy and Realistic Reflection, 2025)
Is it possible to think beyond the structuring and directing influences of thought-shaping? Or, phrased differently, how can thought-shaping be genuinely free and creative? My response in this essay is that we must move beyond the idea of thought-shaping as mere awareness or critical reflection. As I show, the notion of reflection itself has raised some philosophical issues of its own. Notably issues surrounding the limits of reason, the effective presence of biases, and overreliance on the notion of historical experience as they were transmitted from Kant to Hegel are critically discussed, with the aim of identifying a new direction to think about reflection. The development of reflection is examined via the thought of Gadamer, mainly through his hermeneutic conception of experience. After discussing these issues, I develop the notion of refraction, expanding on the concept as it was developed by Bergson. I explain how refraction relies on the appreciation of difference, thereby reorienting the entire field of thinking and overcoming the limitations inherent in the notion of reflection. This differentiating feature turns refraction into a creative and generative process. Concluding, I discuss how refraction supports free thinking by appealing to the notion of creative piety and the embrace as well as usage of limitations in thinking.